Efficacy of Skill DevelopmentTechniques: Empirical Evidence - Eijaz Gul (Journal of Education and Educational Development, 2020)
Making students skillful is the ultimate aim of teaching. The teacher who feel that their jobs are over once they explain and demonstrates the lesson in the class is certainly on the defective side of thinking. Rather,students must be guided towardsthe objectives of learning demonstrated through modeling, and given ample practice to handle learning independently. This paper elucidates various techniques available forskill development by studying the case of 75 students. Their views regarding learning were gathered through a questionnaire. A statistical analysis of their views was carried out, after which they were given a skill to practice through a selected technique which they considered asthe most effective technique for skill development. It was empirically concluded thatstudentslearned the skill more rapidly when they are allowed to use their initiative and judgment in a mutual practice technique of skill development. At the end, guidelines for effective skill development have been suggested which could be adopted by teacher for skill training of students
Keywords: skill development; teaching techniques; teacher efficiency